Enhancement of humoral immunity by the type II heat-labile enterotoxin LT-IIb is dependent upon IL-6 and neutrophils. Issue 2 (8th April 2016) - Greene, Christopher J; Hu, John C; Vance, David J; Rong, Yinghui; Mandell, Lorrie; King-Lyons, Natalie; Masso-Welch, Patricia; Mantis, Nicholas J; Connell, Terry D
Abstract : Augmented and accelerated production of Ag-specific Abs by the i.d. adjuvant LT-IIb requires recruitment of neutrophils and expression of IL-6. Abstract: LT-IIb, a type II heat-labile enterotoxin produced by Escherichia coli, is a potent intradermal adjuvant that enhances immune responses to coadministered antigens. Although the immune mechanisms that promote this augmented immune response have not been well defined, prior intradermal immunization experiments suggested that early cellular and immunomodulatory events at the site of immunization modulated the augmentation of antigen-specific immune responses by LT-IIb. To investigate that hypothesis, mice were intradermally immunized with a recombinant ricin vaccine, a prospective toxin subunit antigen, in the presence and absence of LT-IIb. Analysis of tissue-fluid collection, coupled with histologic sections from the site of intradermal immunization, revealed that a single dose of LT-IIb induced local production of interleukin 6 and promoted a regional infiltration of neutrophils. The adjuvant effects of LT-IIb were abrogated in interleukin 6–deficient mice and when mice were depleted of neutrophils by pretreatment with anti-Ly6G. Overall, these data firmly demonstrated that LT-IIb, when used as an intradermal adjuvant, recruits neutrophils and is a potent rapid inducer of interleukin 6.